Konsep Qana’ah dalam Mewujudkan Keluarga Harmonis Perspektif Alquran - Irnadia Andriani; Ihsan Mz (NALAR, 2019)
This article aims to discuss the concept of Qana'ah in the Qur'an which is used as a solution to alleviate disharmony problems in the family. Disharmony referred to here is focused on economic issues. The rise of conflicts that occur between husbands and wives is usually caused by a lack of gratitude for the blessings and provisions that Allah has given. Therefore, researchers offer the concept of Qana'ah as a solution to the problem. Because Qana'ah in its sense is to feel enough for what Allah has given. So that they are able to distance themselves from greed. The nature of Qana'ah bases the understanding that the sustenance obtained has become the provision of Allah SWT. This study uses the library research method that collects data from various kinds of literature. The results of this study provide recommendations to many parties to ground the concept of Qana'ah as a way out of family disharmony today.Artikel ini bertujuan untuk membahas tentang konsep Qana’ah dalam Alquran yang digunakan sebagai solusi mengentaskan persoalan disharmoni dalam keluarga. Disharmoni yang dimaksud di sini difokuskan pada persoalan ekonomi. Maraknya konflik yang terjadi antara suami istri biasanya disebabkan oleh kurangnya rasa syukur atas nikmat dan ketentuan yang telah Allah Swt. berikan. Oleh karenanya, peneliti menawarkan konsep Qana’ah sebagai jalan keluar atas persoalan tersebut. Sebab Qana’ah dalam pengertiannya yaitu merasa cukup atas apa yang telah dikaruniakan Allah Swt. sehingga mampu menjauhkan diri dari sifat tamak. Sifat Qana’ah mendasarkan pemahaman bahwa rezeki yang didapatkan sudah menjadi ketentuan Allah Swt. Penelitian ini menggunakan metode library research (kajian pustaka) yang mengumpulkan data-data dari berbagai macam literatur. Hasil dari penelitian ini memberikan rekomendasi kepada banyak pihak untuk membumikan konsep Qana’ah sebagai jalan keluar terhadap disharmoni keluarga dewasa ini.Kata Kunci: Qana’ah, Ikhtiar, Keluarga, Harmonis, Alquran